2010
DOI: 10.1097/cad.0b013e32833a5c51
|View full text |Cite
|
Sign up to set email alerts
|

Indwelling central venous access port insertion during bevacizumab-based therapy

Abstract: Indwelling central venous catheters and implantable port systems are widely used in the care of patients with cancer. Bevacizumab, a humanized monoclonal antibody against vascular endothelial growth factor, significantly prolongs survival when added to intravenous 5-fluorouracil-based chemotherapy as first-line treatment for metastatic colorectal cancer. It has also been shown to be of value in a range of other malignant diseases. Some elements of the toxicity profile of bevacizumab, however, such as bleeding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…Erinjeri et al showed that the frequency of wound dehiscence was significantly higher in patients who used BEV within 14 days of implantation [ 12 ]. Meanwhile, Grenader, et al evaluated 20 patients in whom a CV port was implanted during BEV therapy and found no adverse events despite the early administration of BEV [ 13 ]. Consistent with this report, there were no BEV-related complications regardless of the timing of BEV treatment initiation; additionally, we found that the frequency of total complications was not affected by BEV treatment initiation early after CV port implantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Erinjeri et al showed that the frequency of wound dehiscence was significantly higher in patients who used BEV within 14 days of implantation [ 12 ]. Meanwhile, Grenader, et al evaluated 20 patients in whom a CV port was implanted during BEV therapy and found no adverse events despite the early administration of BEV [ 13 ]. Consistent with this report, there were no BEV-related complications regardless of the timing of BEV treatment initiation; additionally, we found that the frequency of total complications was not affected by BEV treatment initiation early after CV port implantation.…”
Section: Discussionmentioning
confidence: 99%
“…Within 10–14 days after CV port implantation, the frequency of wound dehiscence may increase, as reported previously [ 11 , 12 ]. Meanwhile, a study that evaluated 20 patients in whom a CV port was implanted during BEV therapy has shown that there are no adverse events despite the early administration of BEV [ 13 ]. Japanese guidelines for CV port placement have not reached a consensus on when is the appropriate BEV administration time after CV port implantation [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…16 It was reported that the absolute risk of wound dehiscence was 2.1% versus 0.5% when the TIVAD was placed during the previous week. 5 It was found that the use of bevacizumab has affected the wound opening in Zawacki et al's 15 On the other hand, Grenader et al 17 found that a TIVAD may safely be inserted a short time before or during bevacizumab treatment. Grenader et al 17 reported that bevacizumab therapy had no effect on the wound healing process whereas Erinjeri et al 18 reported that the risk of wound dehiscence was inversely proportional to the interval between bevacizumab administration and TIVAD placement, with significantly higher risk seen when the interval is less than 14 days.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of granulocyte-colony stimulating factor (G-CSF) was not consistent across study arms in most of these studies. Despite its deleterious impact on wound healing, no increased periprocedural morbidity (including infections at the insertion site) has been observed after placing long-term central venous catheters in bevacizumab-treated patients [41], although a more recent study has provided conflicting results [42].…”
Section: Available Clinical Datamentioning
confidence: 99%